Reverse mortgages and linked securities the complete guide to risk, pricing, and regulation - Bhuyan, Vishaal B., 1983- (Wiley finance series ;, 2011)
"An institutional investor's guide to the burgeoning field of reverse mortgage securitization. Reverse Mortgages and Linked Securities is a contributed title comprising many of the leading minds in the Home Equity Conversion Mortgages (HECM) industry, including reverse mortgage lenders, institutional investors, underwriters, attorneys, and regulators. This book begins with a brief history of reverse mortgages, and quickly moves on to discuss how the industry has evolved-detailing the players in these markets as well as the process. It discusses the securitization of reverse mortgages and other linked securities and includes coverage of pricing techniques and risk mitigation. This reliable resource also takes the time to cover the current regulatory environment of the HECM market, which is constantly changing due to the current state of the real estate market. Highlights specific strategies that will allow institutional investors to benefit from the resurgence of reverse mortgages and linked securities. One of the only guides to reverse mortgages and linked securities targeted towards institutional investors interested in securitized products. If you want to make the most of reverse mortgages and linked securities, take the time to read this book."--